Performance of Arch-Style Road Crossing Structures from Relative Movement Rates of Large Mammals - Andis, A. Z.; Huijser, Marcel P.; Broberg, Len (Frontiers in Ecology and Evolution, 2017)
In recent decades, an increasing number of highway construction and reconstruction projects have included mitigation measures aimed at reducing wildlife-vehicle collisions and maintaining habitat connectivity for wildlife. The most effective and robust measures include wildlife fences combined with wildlife underpasses and overpasses. The 39 wildlife crossing structures included along a 90 km stretch of US Highway 93 on the Flathead Indian Reservation in western Montana represent one of the most extensive of such projects. We measured movements of large mammal species at 15 elliptical arch-style wildlife underpasses and adjacent habitat between April and November 2015. We investigated if the movements of large mammals through the underpasses were similar to large mammal movements in the adjacent habitat. Across all structures, large mammals (all species combined) were more likely to move through the structures than pass at a random location in the surrounding habitat. At the species level, white-tailed deer (Odocoileus virginianus) and mule deer (O. hemionus) used the underpasses significantly more than could be expected based on their movement through the surrounding habitat. However, carnivorous species such as bear (Ursus americanus) and coyote (Canis latrans) moved through the underpasses in similar numbers compared to the surrounding habitat.